Binding activity, structure, and immunogenicity of synthetic peptides derived from Plasmodium falciparum CelTOS and TRSP proteins (2012)
Several sporozoite proteins have been associated with Plasmodium falciparum cell traversal and hepatocyte invasion, including the cell-traversal protein for ookinetes and sporozoites (CelTOS), and thrombospondin-related sporozoite protein (TRSP). CelTOS and TRSP amino acid sequences have been finely mapped to identify regions specifically binding to HeLa and HepG2 cells, respectively. Three high-activity binding peptides (HABPs) were found in CelTOS and one HABP was found in TRSP, all of them having high ?-helical structure content. These HABPs' specific binding was sensitive to HeLa and HepG2 cells' pre-treatment with heparinase I and chondroitinase ABC. Despite their similarity at three-dimensional (3D) structural level, TRSP and TRAP HABPs located in the TSR domain did not compete for the same binding sites. CelTOS and TRSP HABPs were used as a template for designing modified sequences to then be assessed in the Aotus monkey experimental model. Antibodies directed against these modified HABPs were able to recognize both the native parasite protein by immunofluorescence assay and the recombinant protein (expressed in Escherichia coli) by Western blot and ELISA assays. The results suggested that these modified HABPs could be promising targets in designing a fully effective, antimalarial vaccine. © 2011 Springer-Verlag.